Investigation of the influence of fine particles on the discrete phase density in the numerical modelling of a fluidized bed. Issue 4 (February 2019) - Solovev, S A; Soloveva, O V; Antipin, A V
Abstract: In this paper, we consider methods for selecting effective diameters of solid particles for simulating a fluidized bed using the Eulerian-Eulerian approach in order to describe a multiphase medium. Calculations for modal mean diameter and mean diameter of Sauter were carried out. Studies have also been carried out for the bidisperse composition of the particles, with separation into coarse and fine fraction. The results of the numerical simulation were compared with the data from experimental studies.